SURVIVAL STRATEGIES AND HYBRID IDENTITY CONSTRUCTION AS PORTRAYED ON LONDOKAMPUNG’S VIDEOS - Anjanillah, Farah (Annual International Conferences on Language, Literature, and Media, 2021)
A group of people dispersing transnationally is called diaspora (Chiang, 2010; Wei & Hua, 2013). Moving to the host country means adjusting the cultures and language(s) to survive. Viewing this phenomenon, the researcher was intrigued to carry out an inquiry exploring the survival strategies and hybrid identity construction on Londokampung ’s videos. The data of this study were in the form of utterances exhibiting survival strategies and hybrid identity formation. The data were obtained through Londokampung youtube channel. The findings uncover three survival strategies employed; 1) adaptation, 2) integration, and 3) latency. Adaptation strategy is done by creating Indonesian nicknames to be readily accepted in the host community. Meanwhile, integration strategy embeds hybrid loanword and linguistic hybridity such as code-switching and code-mixing. Hybrid loanword is opted due to non-structural and structural motive (Weinreich, 1968). Code-switching is done for two factors; specifying the addressee and excluding the participants. Meanwhile, reiteration and lacking of equivalent word become the two points underlying the use of code-mixing. Ultimately, in terms of latency, Cak Dave constructs hybrid identity to negotiate his “in-between-ness”